2010
DOI: 10.1186/1471-2458-10-382
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and methods of the European Study on Cardiovascular Risk Prevention and Management in Daily Practice (EURIKA)

Abstract: BackgroundThe EURIKA study aims to assess the status of primary prevention of cardiovascular disease (CVD) across Europe. Specifically, it will determine the degree of control of cardiovascular risk factors in current clinical practice in relation to the European guidelines on cardiovascular prevention. It will also assess physicians' knowledge and attitudes about CVD prevention as well as the barriers impeding effective risk factor management in clinical practice.Methods/DesignCross-sectional study conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 27 publications
1
37
0
6
Order By: Relevance
“…Este es un estudio transversal, con datos obtenidos durante el seguimiento de la cohorte de mayores del Estudio de Nutrición y Riesgo Cardiovascular en España (ENRICA) (18). La cohorte se estableció en 2008-2010, con 2.519 individuos seleccionados a través de muestreo aleatorizado de la población española de 60 años o más.…”
Section: Metodología Participantes Y Diseñounclassified
“…Este es un estudio transversal, con datos obtenidos durante el seguimiento de la cohorte de mayores del Estudio de Nutrición y Riesgo Cardiovascular en España (ENRICA) (18). La cohorte se estableció en 2008-2010, con 2.519 individuos seleccionados a través de muestreo aleatorizado de la población española de 60 años o más.…”
Section: Metodología Participantes Y Diseñounclassified
“…The study protocol was approved by the appropriate clinical research ethics committee in each participating country, and all patients provided signed informed consent. The methods for the study have been reported in detail elsewhere [28]. Briefly, the study recruited patients with at least one risk factor for CVD, but no history of cardiovascular events.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Briefly, the study recruited patients with at least one risk factor for CVD, but no history of cardiovascular events. The study sample was selected in a two-step process that involved recruitment of physicians and their patients [28,29]. In the first stage, a random sample of primary care physicians and specialists involved in CVD prevention, stratified by age, sex and specialty, were selected for invitation to participate using the OneKey database (Cegedim Dendrite, Boulogne-Billancourt, France).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Большая часть имеющейся информации о контроле ФР касается пациентов с доказанными ССЗ или пациентов с высоким ССР, в т.ч. среди больных сахарным диабетом (СД) [4]. При этом такие исследования как REACH (The Reduction of Aterothrombosis for Continued Health) registry или EUROASPIRE (European Action on Secondary Prevention through Intervention to Reduce Events) показали высокую распространенность ФР (главным образом связанных с образом жизни) и явную недостаточность их контроля (причем при отсутствии отчетливой положительной динамики с 1995г) как среди амбулаторных пациентов, так и среди больных, госпитализированных по поводу атеротромботических осложнений [5][6][7].…”
unclassified
“…С учетом этих обстоятельств было организовано исследование EURIKA (European Study on Cardiovascular Risk Prevention and Management in Daily Practice) [11], призванное оценить состояние первичной профилактики ССЗ в 12 странах Европы: Австрии, Бельгии, Великобритании, Германии, Греции, Испании, Норвегии, Российской Федерации (РФ), Турции, Франции, Швеции, Швейцарии, различающихся по климатогеографическим условиям, уровню экономического развития и принципам организации медицинской помощи населению.…”
unclassified